2022
DOI: 10.1002/ehf2.13801
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of heart failure patients with reverse left ventricular remodelling post‐angiotensin receptor blockers/neprilysin inhibitors therapy

Abstract: AimsTo assess the effect of angiotensin receptor blockers/neprilysin inhibitors (ARNI) on left ventricular (LV) ejection fraction (LVEF) and LV dimensions in a real-life cohort of heart failure and reduced ejection fraction (HFrEF) patients, while analysing patient characteristics that may predict reverse LV remodelling. Methods and resultsThe ARNI-treated HFrEF patients followed at a single tertiary medical centre HF-outpatient clinic were included in the study. Clinical and echocardiographic parameters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Of note, CRT patients in our study were non-responders and therefore our results may not apply to all CRT patients. Indeed, the absence of CRT was a predictor of reverse LV remodeling after the initiation of SV in a registry study on patients with HFrEF including 43% with an implanted CRT device [ 18 ]. The authors’ proposed explanation for this finding was that the potential myocardial reserve was already realized by cardiac resynchronization, thereby leaving no room for further improvement with SV.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, CRT patients in our study were non-responders and therefore our results may not apply to all CRT patients. Indeed, the absence of CRT was a predictor of reverse LV remodeling after the initiation of SV in a registry study on patients with HFrEF including 43% with an implanted CRT device [ 18 ]. The authors’ proposed explanation for this finding was that the potential myocardial reserve was already realized by cardiac resynchronization, thereby leaving no room for further improvement with SV.…”
Section: Discussionmentioning
confidence: 99%
“…One prospective study on patients with HFrEF demonstrated the effect of treatment with ARNI on both LV and LA reverse remodeling, despite the inclusion of patients with long-lasting disease [ 12 ]. In addition, Maizels et al [ 13 ] reported that the effect of ARNI therapy on CRR was greater in selective patients, especially in those receiving ARNI treatment within 3 years from HF diagnosis, thereby demonstrating that they had greater LVEF improvement than other patients. Similarly, our study showed that increase of LVEF in the de novo group was approximately 1.5 times higher than that in the prior HF group (12.0 vs. 7.4%, p = 0.010).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin‐converting enzyme inhibitors (ACEIs), angiotensin II receptor blockers (ARBs), 3–6 beta‐blockers, 7–10 and mineralocorticoid receptor antagonists (MRAs) 11,12 have been recognized as the cornerstones in the pharmacologic treatment of HF. Recent studies have reported that compared with enalapril, angiotensin receptor–neprilysin inhibitors (ARNI) reduce morbidity and mortality by improving the ejection fraction (EF) and inducing left ventricular (LV) reverse remodelling in patients with HF with reduced ejection fraction (HFrEF) 13–19 . Currently, HF guidelines recommend ARNI as the frontline therapy for patients with HFrEF 20–22 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that compared with enalapril, angiotensin receptor–neprilysin inhibitors (ARNI) reduce morbidity and mortality by improving the ejection fraction (EF) and inducing left ventricular (LV) reverse remodelling in patients with HF with reduced ejection fraction (HFrEF). 13 , 14 , 15 , 16 , 17 , 18 , 19 Currently, HF guidelines recommend ARNI as the frontline therapy for patients with HFrEF. 20 , 21 , 22 However, whether ARNI remain effective in patients who achieved an improvement in LV systolic function or significant LV reverse remodelling after a certain period of treatment as well as in patients without these improvements is unclear.…”
Section: Introductionmentioning
confidence: 99%